The Peculiarities of Elder Teenager’s Christian Identity - Martišauskienė, Elvyda (Acta Paedagogica Vilnensia, 2003)
The identity is an important part of the formation of teenagers, because it enables us to connect ourselves with an entire Existence. And looking for identity is the most important sign of the adolescence. The attitudes to the world outlook, toward ourselves and the aims express the identity. The teenagers of 13-15 years old relate the identity most with the attitudes to the world outlook. The 79.9 percent of the interrogated children choose the idealistic world outlook. Though only 1,4-2 percent of them base their attitudes to themselves and their aims on the Christian values. The highest moral values very little add to the identity. The religious identity has still been working its way to the life of teenagers. The identity is mainly under the influence of gender (it is higher among girls) and school. The factor of the formation of attitudes to the world outlooks and the internalisation of sanctity, sensitiveness, altruism and feeling of beauty are very important.